Customised Dumon Y‐Stent With Reversed Orientation for Management of Complex Airway Obstruction in Endobronchial Non‐Small‐Cell Lung Cancer: Clinical Image of a Successful Airway Salvage - Yuki Takigawa; Ken Sato; Hiromi Watanabe; Satoko Ido; Takeru Ichikawa; Shoichiro Matsumoto; Suzuka Matsuoka; Jun Nishimura; Kenichiro Kudo; Keiichi Fujiwara; Takuo Shibayama (Respirology Case Reports)
ABSTRACT A customised Dumon Y‐stent was successfully used to manage an obstructive, bleeding endobronchial non‐small‐cell lung cancer. Owing to the unusually sharp left main bronchus angle, the stent was reversed to achieve optimal anatomical alignment. The right limb was shortened and sealed, creating a blind end. Airway patency was effectively maintained.